Euphorbiaceae endémicas del Perú - León, Blanca (2006)
The Euphorbiaceae are represented in Peru by 61 genera and 323 species (Brako & Zarucchi, 1993; Ulloa Ulloa et al., 2004), mainly shrubs and trees. Here we recognize as Peruvian endemics 47 species and two varieties in 19 genera. Croton is the genus with the largest number of endemic species. Endemic Euphorbiaceae are found in several regions, including Humid Lowland Amazonian Forests, Mesoandean and Very Humid Montane Forests, between 110 and 3200 m elevation. We applied IUCN categories and criteria to 33 taxa. Three endemic Euphorbiaceae species have been registered to date within Peru’s protected areas system.